Investigation of extracellular polymeric substances (EPS) in four types of sludge: Factors influencing EPS properties and sludge granulation. (April 2021) - Liu, Xiaoying; Liu, Jie; Deng, Dongkun; Li, Renjie; Guo, Chao; Ma, Jinxia; Chen, Ming
Graphical abstract: Abstract: Extracellular polymeric substances (EPS) released by bacteria play a crucial role in microbial aggregation during wastewater treatment. Various environmental factors including substrate, anaerobic and aerobic conditions might contribute to the formation and properties of EPS, and thereby affect the properties of microbial aggregation and sludge. To reveal the relationship between these environmental factors and EPS properties, the characteristics of EPS generated in four types of sludge were investigated, including anammox granular sludge (ANMX), aerobic granular sludge (AGS) fed with glucose as carbon source (AGS-GLUC), AGS fed with liquor wastewater as carbon source (AGS-LIQ), and flocculent sludge from a real sewage plant (FLOC). Results indicated a positive correlation of EPS contents with granulation of sludge. As the dominant content of EPS, an increased proteins (PN) concentration facilitated the formation of microbial aggregates and the granulation of sludge. Bacteria in anaerobic environment (i.e., ANMX) or in aerobic environment with easily biodegradable carbon sources (i.e., AGS-GLUC) would generate more PN and EPS; yet, these conditions restrained the generation of humic acid (HA). The sludge from the sewage treatment plant (i.e., FLOC) had the lowest EPS and PN content, but the highest HA, showing flocculent structure sludge. In addition, a higher protein/polysaccharide (PN/PS) ratio and a lower zeta potential of EPS were conductive to sludge granulation. The hydrophobicity of EPS confirmed via analysis of chemical structures by FTIR would improve the microbial aggregation.